Technical parameters and mental toughness in tennis players - Türk, S.; Taskin, H.; Taskin, M. (International Journal of Applied Exercise Physiology, 2019)
The aim of this study is to examine the relationship between technical parameters and mental toughness in tennis players. The mean age was 13,60 ± 1,75 years for 25 women and mean age was 13,33 ± 2,40 years for 24 men tennis players participated as volunteers. The International Tennis Number (ITN) test was applied to measure the technical skills, and to determine the mental toughness levels, a tennis-specific mental toughness questionnaire was applied. As results, technical tests (ground shots depth - power test, vole strokes depth - power test, ground stroke sensitivity - power test and service strokes) and mental toughness (imagery, motivation and self-confidence) is seen in a statistically negative relationship. There was no statistically significant relationship between depth - power test and depth - power test and energy and attention subscales. On the other hand, it was found that there was a positive relationship between the technical tests and the precision-strength test and the service strokes test and the sub-dimensions of mental toughness. In addition, there was a negative correlation between ITN level and attention subdimension, whereas there was a positive correlation between imagination, motivation and self-confidence. However, there was no a significant relationship between ITN level and energy sub-dimension. In conclusion, when mental toughness increases, it is seen that ITN levels of tennis players are increasing and considering that the athletes with good mental toughness can perform better, it is concluded that the coaches should include mental toughness studies in the training programs.